Draft Five Year Plan 1978-83 Agriculture - Government of Madhya Pradesh (Government of Madhya Pradesh, 1978)
The Draft Five-Year Plan (1978-83) for agriculture in Madhya Pradesh highlights the central role of agriculture in the state’s economy, contributing 55% of the net domestic product and employing 80% of the workforce, with 5.3 million farming families cultivating 18.5 million hectares of land. Despite being generally self-sufficient and a major producer of food grains and pulses, the state faces challenges due to variable monsoon rains, low irrigation coverage (11% of cropped area), a high proportion of marginal and small farmers, and significant tribal populations practicing primitive agriculture. Key crops include rice, sorghum, maize, wheat, barley, and oilseeds, with pulses contributing about 20% to national production. Irrigation potential, particularly from river valleys and groundwater, is underutilized, while heavy black cotton soils and hilly, erosion-prone tribal areas pose productivity challenges. Agricultural development priorities include exploiting irrigation potential, soil and moisture conservation, improving cropping intensity, diversifying production patterns, and raising cash crops and horticulture. A review of the 1974-77 period indicates a growth rate of 2.27% per year in production, with frequent shortfalls due to droughts, underutilized irrigation, delayed pumping set installations, rising fertiliser costs, and limited access to short-term credit through cooperative societies. Crop yields remain below national averages, particularly for rainfed areas, emphasizing the need for targeted technological interventions, irrigation expansion, and financial support to achieve higher productivity and stabilize agricultural output.
Sixth Five Year Plan 1978-83 Agricultural Development in Madhya Pradesh
Sixth Five Year Plan 1978-83 Agricultural Development in Madhya Pradesh
Keywords: Agriculture; Madhya Pradesh; Food-Grain Production; Irrigation Potential; Crop Yields; Rainfed Farming; Marginal Farmers; Tribal Agriculture; Fertiliser Use; Credit Availability; Black Cotton Soils; Agricultural Development